2022
DOI: 10.1093/cercor/bhac350
|View full text |Cite
|
Sign up to set email alerts
|

Precision fMRI reveals that the language-selective network supports both phrase-structure building and lexical access during language production

Abstract: A fronto-temporal brain network has long been implicated in language comprehension. However, this network’s role in language production remains debated. In particular, it remains unclear whether all or only some language regions contribute to production, and which aspects of production these regions support. Across 3 functional magnetic resonance imaging experiments that rely on robust individual-subject analyses, we characterize the language network’s response to high-level production demands. We report 3 nov… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(63 citation statements)
references
References 143 publications
3
42
2
Order By: Relevance
“…Furthermore, the language network responds to stimulus features rather than task demands, as evidenced by i) similar responses to linguistic input under passive listening/reading and task-driven conditions [e.g., Diachek et al, 2020] and ii) similar patterns of fluctuations across participants when they process naturalistic linguistic stimuli [e.g., Wilson et al, 2008, Lerner et al, 2011, Silbert et al, 2014, Blank and Fedorenko, 2017. Further, the language network is sensitive to linguistic regularities at all levels: from phonological/sub-lexical, to word level, to phrase/sentence level [Bautista and Wilson, 2016, Blank et al, 2016, Fedorenko et al, 2011 and supports linguistic operations that are related to both the processing of word meanings and those related to combinatorial semantic and syntactic processing , Hu et al, 2022b. This consistent recruitment for language across a broad range of conditions, as well as the fact that damage to the language network leads to linguistic deficits [e.g., Bates et al, 2003, Broca, 1865, Damasio, 1992, Mesulam, 2001, Mesulam et al, 2014, Saffran, 2000, Wernicke, 1874, Wilson et al, 2019, indicates that this set of regions stores our linguistic knowledge representations-a set of mappings between linguistic forms and meanings.…”
Section: The Language Network In the Human Brainmentioning
confidence: 88%
See 1 more Smart Citation
“…Furthermore, the language network responds to stimulus features rather than task demands, as evidenced by i) similar responses to linguistic input under passive listening/reading and task-driven conditions [e.g., Diachek et al, 2020] and ii) similar patterns of fluctuations across participants when they process naturalistic linguistic stimuli [e.g., Wilson et al, 2008, Lerner et al, 2011, Silbert et al, 2014, Blank and Fedorenko, 2017. Further, the language network is sensitive to linguistic regularities at all levels: from phonological/sub-lexical, to word level, to phrase/sentence level [Bautista and Wilson, 2016, Blank et al, 2016, Fedorenko et al, 2011 and supports linguistic operations that are related to both the processing of word meanings and those related to combinatorial semantic and syntactic processing , Hu et al, 2022b. This consistent recruitment for language across a broad range of conditions, as well as the fact that damage to the language network leads to linguistic deficits [e.g., Bates et al, 2003, Broca, 1865, Damasio, 1992, Mesulam, 2001, Mesulam et al, 2014, Saffran, 2000, Wernicke, 1874, Wilson et al, 2019, indicates that this set of regions stores our linguistic knowledge representations-a set of mappings between linguistic forms and meanings.…”
Section: The Language Network In the Human Brainmentioning
confidence: 88%
“…Human language processing draws on a set of interconnected brain areas in the frontal and temporal lobes (typically in the left hemisphere). This 'language network' supports both comprehension (spoken, written, and signed; e.g., Deniz et al, 2019, Fedorenko et al, 2010, MacSweeney et al, 2002, Regev et al, 2013, Scott et al, 2017 and production Menenti et al, 2011, Hu et al, 2022b. Furthermore, the language network responds to stimulus features rather than task demands, as evidenced by i) similar responses to linguistic input under passive listening/reading and task-driven conditions [e.g., Diachek et al, 2020] and ii) similar patterns of fluctuations across participants when they process naturalistic linguistic stimuli [e.g., Wilson et al, 2008, Lerner et al, 2011, Silbert et al, 2014, Blank and Fedorenko, 2017.…”
Section: The Language Network In the Human Brainmentioning
confidence: 99%
“…In this fMRI study, we aimed to study syntactic processing in spontaneous production and comprehension in order to understand whether and how they differ. Previous studies found shared neural resources for production and comprehension (Menenti et al, 2011;Segaert et al, 2012) and a similar network for processing syntactic complexity across modalities (Giglio et al, 2022;Hu et al, 2022). At the same time, production was found to elicit larger responses to syntactic complexity than comprehension, especially in the left inferior frontal gyrus (LIFG) (Giglio et al, 2022;Hu et al, 2022;.…”
Section: Introductionmentioning
confidence: 78%
“…Previous studies found shared neural resources for production and comprehension (Menenti et al, 2011;Segaert et al, 2012) and a similar network for processing syntactic complexity across modalities (Giglio et al, 2022;Hu et al, 2022). At the same time, production was found to elicit larger responses to syntactic complexity than comprehension, especially in the left inferior frontal gyrus (LIFG) (Giglio et al, 2022;Hu et al, 2022;. The differential sensitivity to complexity between modalities may be due to two main factors: 1) Speaking is a form of action, unlike the more passive process of listening.…”
Section: Introductionmentioning
confidence: 78%
“…In most analyses, we treat the language network as an integrated whole given that these regions a) have similar functional profiles with respect to their selectivity for language (e.g., Fedorenko et al, 2011; Fedorenko & Blank, 2020) and their role in lexico-semantic and combinatorial processing during language comprehension and production (e.g., Fedorenko et al, 2010, 2016, 2020; Blank et al, 2016; Bautista & Wilson, 2016; Hu, Small et al, 2022) and b) exhibit strong inter-region correlations in their activity during naturalistic cognition paradigms (e.g., Blank et al, 2014; Paunov et al, 2019; Braga et al, 2020). However, for some analyses, we additionally fitted models that predicted the BOLD response in each language fROI separately in order to explore potential differences between fROIs.…”
Section: Methodsmentioning
confidence: 99%